Using the Middle Ages in Modern-day Croatia - Budak, Neven (2009)
The author analyses different ways in which Middle Ages have been used in modern-day Croatia, i.e. during the past twenty years. He analyses motifs on stamps and banknotes, street names and monuments, and tries to show the changing attitudes towards the medieval past among politicians and others.
Projekt MZOS
ENG